Analisis Kadar C-Organik Pupuk Organik Padat dari Limbah Bayam - Rahmi Pratiwi, Anisah Fitri; Imamah, Nanda Sofa; Putra Suryadi, Gian Firdaus; Muhaimin, Fitriari Izzatunnisa (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
Composting is one way of making organic waste into a new product in the form of humus made from organic waste from plant and animal waste. This research was carried out in July-November 2023 at the final disposal site (TPA) in Pucuk Village, Mojokerto. The aim of this research is to analyze the benefits and content of C-Organic in solid organic fertilizer from spinach waste. The research method was carried out by measuring and analyzing the C-Organic content in fertilizer using a UV-Vis spectrophotometer. The results obtained from research testing the C-Organic content of 6.5% are still relatively low, and do not meet the quality standards of SNI 7763:2018 and Decree of the Minister of Agriculture of the Republic of Indonesia Number 261/KPTS/ SR.310/M/4/2019 which states C-organic content of at least 15%.